Effect of Pulse Repetition Rate on Micro Hardness on the Surface and Cross Section of Gray Cast Iron by using ND-YAG Laser - Shahada, A.; S. Alwanb, B. Abbas; A. Abedc, Kadhemm. (Anbar Journal of Engineering Sciences, 2019)
This work, studied the effect of pulse repetition rate on the micro hardness for each of the surface and cross section by using pulsed ND-YAG laser with laser parameters (Energy = 4.12J).The distance off between the output nozzle and the minimum spot size on the surface of sample was (12mm),and pulse duration was (1.8ms).The results showed that the micro hardness increased after laser treatment ,but the micro hardness decreased with increase pulse repetition rate for both the surface and cross section of the pulses. The micro hardness increased as moving away from the molten zone towards the end of the pulses at the heat affected zone due to increase in cooling rate.